TG CHARACTERISTICS OF WOOL AND COTTON FIBERS IMPREGNATED WITH AZO-DYES - Pirzada, T.; Saleem, M.; Qadeer, R.; Khurshid, S. J. (The Nucleus, 2020)
The impregnation of AV17, AB90, AR1 and DR80 dyes on wool and on cotton AV17 and DR80 was carried out at optimized conditions of shaking time and pH for the maximum uptake of the dyes by the fibers. The effects of the dyes impregnation on thermal oxidation of wool and cotton fibers were studied by employing thermogravimetric analysis. The results show that the weight loss of wool fiber was in a single step and the impregnation of AR1 on wool fiber results in a significant decrease in the decomposition temperature. The impregnation of AV17 and DR80 on wool fiber changes the nature of the thermogravimetric pattern and two steps weight losses were observed as compared to the single step weight loss observed in virgin wool fiber. The impregnation of AV17 and DR80 dyes on cotton fiber does not change the nature of the thermogravimetric behavior of the fiber and two stage weight loss were observed for both virgin and impregnated cotton fiber. It has been found out that impregnation only affects the weight loss in both the steps. These results are important in relation to the dyeing of wool and cotton fibers.